2007
DOI: 10.1227/01.neu.0000249248.55923.ec
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Accuracy of Cyberknife Spinal Radiosurgery Using Skeletal Structure Tracking

Abstract: The Xsight spine tracking system is practically important because it is accurate and eliminates the use of implanted fiducials. Experience has shown this technology to be robust under a wide range of clinical circumstances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(71 citation statements)
references
References 70 publications
(26 reference statements)
2
68
0
1
Order By: Relevance
“…A well-calibrated CyberKnife V R system typically performs static E2E tests on the level of 0.3-0.7 mm. 41,45,46 Since it is very time-consuming to perform E2E tests for all tracking modalities and path combinations every month, it is recommended that one intracranial and one extra-cranial E2E be performed at least monthly. These tests need to be cycled through each path and tracking method combination that is in clinical use.…”
Section: Iiic2 Isocentric End-to-end (E2e) Testmentioning
confidence: 99%
“…A well-calibrated CyberKnife V R system typically performs static E2E tests on the level of 0.3-0.7 mm. 41,45,46 Since it is very time-consuming to perform E2E tests for all tracking modalities and path combinations every month, it is recommended that one intracranial and one extra-cranial E2E be performed at least monthly. These tests need to be cycled through each path and tracking method combination that is in clinical use.…”
Section: Iiic2 Isocentric End-to-end (E2e) Testmentioning
confidence: 99%
“…The SRS treatment procedure has been described in detail recently [15,[20][21][22]. The CyberKnife and the skeletal structure tracking software (X SIGHT , Accuray Inc.), were used for spinal radiosurgery in all patients.…”
Section: Methodsmentioning
confidence: 99%
“…The CyberKnife and the skeletal structure tracking software (X SIGHT , Accuray Inc.), were used for spinal radiosurgery in all patients. Previous studies have shown the feasibility and submillimetre accuracy of this fiducial-free, frameless method [15,20,21,23,24]. Planning and delivery of treatment were performed as outpatient procedures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Xsight spine tracking system [8] matches stereoscopic live images of the spinal region of interest (ROI) with synthetic reference images (digitally reconstructed radiographs -DRRs) to determine the position of the spinal target. The ROI typically includes three to four adjacent vertebrae.…”
Section: Xsight Spine Tracking (Xst)mentioning
confidence: 99%